Reviewing the Human Capital Performance Stimulants of Private Employees in Indonesia: The Role of Job Satisfaction as a Mediator with a Quantitative Approach - Hery Pandapotan Silitonga; Ady Inrawan; Lenny Dermawan Sembiring; Darwin Lie; Sri Rezeki Putri Tanjung (Research Synergy Foundation, 2021)
The effectiveness of organizations and companies is correlated with human capital performance. Therefore, we require the use of human capital performance as a benchmark for organizations and companies to achieve the vision and mission together. Later, the benchmark will serve as a basis for policymaking on the future maintenance and improvement of human capital performance. This research aims to find out the stimulants that affect the human capital performance of private employees. The quantitative causality approach is used in this study to answer the formulation of research problems and research hypotheses. Next, the researcher tested the hypothesis using Structural Equation Modeling (SEM) based on a variant called Partial Least Square (PLS) and the SmartPLS version 3.0 application as a tool to analyze it. The results of this research conclude that six hypotheses that examine the direct effect of self-leadership, organizational justice, and work environment on work satisfaction obtain positive and significant results. Then self-leadership, teamwork management, and work satisfaction on human capital performance also obtained positive and significant results. In addition, the results of this research also confirm the positive and significant mediating effect of work satisfaction on the indirect impact of self-leadership, organizational justice, and work environment on human capital performance. For further research, the author recommends further researchers develop variables that are suspected to be the main predictors to encourage work satisfaction and human capital performance to provide complete recommendations regarding the development of human resource performance, especially for millennial workers. This study presents a research model related to human capital performance regarding self-leadership, teamwork management, and work satisfaction and the contribution of self-leadership, organizational justice, and work environment to work satisfaction.